Profile of Childbearing Age Women Who are Willing and Unwilling to Undergo VIA (Visual Inspection with Acetic Acid) Examination at the Temindung Samarinda Community Health Center - Dian Nurlita Anggraini; Sulistiawati; Wiradharma, Handy (Jurnal Ilmu Kesehatan, 2024)
Cervical cancer ranks as the eighth most common cancer in women. One method for early detection of precancerous cervical lesions is through Visual Inspection with Acetic acid (VIA). In Samarinda, the Temindung Community Health Center stands out as the sole community health center offering VIA examinations. This study aimed to profile childbearing-age women at the Temindung Samarinda Community Health Center who are willing or unwilling to undergo Visual Inspection with Acetic acid (VIA). The research employed an observational descriptive method. Purposive sampling was the technique used for selecting participants. The respondents comprised 81 childbearing-age women at the Temindung Samarinda Community Health Center. Key variables in this study included education level, knowledge about VIA, and whether they had received information about VIA from health workers. Data were collected through interviews using questionnaires. The findings revealed that 72 respondents (88.89%) were willing to undergo VIA examination, while 9 respondents (11.11%) were not. Among those willing to undergo VIA, the majority were high school-educated, possessed good knowledge about VIA, and had not received information about VIA from health workers. Conversely, the majority of those unwilling to undergo VIA were mostly junior high school-educated, had good knowledge about VIA, and similarly had not received information about VIA from health workers. Keywords: Cervical Cancer, VIA, Childbearing-Age Women